2007
DOI: 10.3177/jnsv.53.75
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Arachidonic Acid Supplementation on Age-Related Changes in Endothelium-Dependent Vascular Responses

Abstract: SummaryThe purpose of the present study was to examine the effects of dietary supplementation of arachidonic acid (ARA) on age-related changes in endothelium-dependent vascular responses. Young male Fisher-344 rats (2-mo-old) and aged rats of the same strain (22-mo-old) were randomly separated into a control diet group (young control, YC; old control, OC) and an ARA-containing diet group (young ARA, YA; old ARA, OA). After a 2-mo feeding period, vascular responses were evaluated using both endothelium-intact a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The conversion of LA to ARA declines with age [5], and the importance of ARA supplementation among the elderly has recently gained increased attention. It has been reported that supplementation with ARA among the elderly improves cognitive response [6] and coronary flow velocity reserve [7] and some animal studies support these findings [8-11]. …”
Section: Introductionmentioning
confidence: 91%
“…The conversion of LA to ARA declines with age [5], and the importance of ARA supplementation among the elderly has recently gained increased attention. It has been reported that supplementation with ARA among the elderly improves cognitive response [6] and coronary flow velocity reserve [7] and some animal studies support these findings [8-11]. …”
Section: Introductionmentioning
confidence: 91%
“…This oil has been used for infant formula worldwide [60]. At the same time, ARA oil is now used for adult humans, especially the elderly, making it possible to investigate the physiological roles and efficacy of ARA [61][62][63][64][65][66][67][68]. Table 5 summarizes the clinical trials reporting changes in ARA composition of blood in adult humans with ARA supplementation [16,17,19,[69][70][71][72][73][74].…”
Section: Ara Source By Fermentation Techniquementioning
confidence: 99%
“…There were no significant differences in endothelium-independent vasodilator responses to sodium nitroprusside in any of the groups. These findings suggest that dietary ARA supplementation improves age-related endothelial dysfunction that leads to various cardiovascular diseases (20). DGLA, dihomo-γ-linolenic acid; ARA, arachidonic acid; EPA, eicosapentaenoic acid; DHA, docosahexaenoic acid.…”
Section: Effects Of Dietary Ara Supplementation On Agerelated Changesmentioning
confidence: 99%